FUNGSI PENGAWASAN DAN PEMERIKSAAN TERHADAP PENGGUNAAN DANA DESA DI KABUPATEN KUANTAN SINGINGI TAHUN 2020 - Yossi Primasthi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
One of the policies adopted to support development in the village is the implementation of fiscal decentralization through the Village Fund to support village development and empowerment. However, in the implementation of the Village Fund, there are concerns from various parties due to indications of fraud (abuse) carried out by elements in the village as evidenced by the many complaints. This is certainly a signal for the government to supervise the Village Funds originating from the APBN so that their management remains in line with applicable regulations. Based on the Regulation of the Minister of Home Affairs (Permendagri) Number 71 of 2015 concerning Policies for Guidance and Supervision within the Ministry of Home Affairs and Regional Governments in 2016, the supervision of village funds is part of the supervision of the Regency / City Regional Inspectorate within the scope of the inspection of Village Government administration. The type of research used in this research is qualitative research. In this study, the data used came from various sources (multiple sources of data) such as interviews, observations, and documents. The results showed that the implementation of the supervisory and inspection functions of the Kuantan Singingi Inspectorate adhered to the existing supervisory SOP and PKPT and PKA which became work guides. The preparation of the PKA and PKPT is quite effective in overcoming the shortage of auditor personnel at the Kuantan Singingi Inspectorate, the elaboration in the PKPT has been arranged in such a way how supervision can run efficiently but the implementation of the supervision and inspection function by the Kuantan Singingi Inspectorate on the use of village funds has not been maximized, namely in the sector. budget, time, and uncooperative village parties, but not many abuses of village funds in Kuantan Singingi District that have reached legal proceedings, only 1 or 2 villages with a percentage of less than 20%. Keywords: Inspectorate, Supervision Function, Village Fund